Mini-TAS as a confirmatory mapping tool for remapping areas with uncertain filarial endemicity to exclude/ include for mass drug administration: A report from field validation in India. - Barsa Baisalini Panda; Kaliannagounder Krishnamoorthy; Arundhuti Das; Hitesh Kumar Jain; Sujata Dixit; Manju Rahi; Nilam Somalkar; Shubhashisha Mohanty; Sanghamitra Pati; Manoranjan Ranjit; Madhusmita Bal (PLoS ONE, 2023)
India has targeted elimination of lymphatic filariasis (LF) through mass drug administration (MDA) by 2027. Mapping of LF endemic areas is a priority for implementation of MDA. Current national LF remapping tool for unsurveyed/uncertain districts, have many limitations. The WHO has recommended a sensitive and rapid remapping protocol (Mini-TAS), that needs validation in Indian setting. Hence, in the present study a comparative assessment of these two protocols (national protocol vs Mini-TAS) was undertaken in two non-MDA districts of Odisha, with unknown filarial endemicity but reporting chronic cases. Purposive sampling was done in five top sites based on filarial case count as per the national protocol. Random 30 cluster survey was done by conducting school based Mini-TAS, Microfilariae (Mf) survey among adults (>10 years) in villages/wards with schools and Molecular Xenomonitoring (MX) of infection in vectors. Costing by activity and items of the surveys was acomplished using itemized cost menu. In Kalahandi, one of the five purposive sampling sites showed Mf prevalence above threshold (> 1%). But except Mini-TAS neither MX nor house-hold Mf survey among adults could detect the infection above the threshold. While in Balangir, Mf prevalence in all purposive sampling sites,Mini-TAS, Mf prevalence among adult and MX were above the respective thresholds confirming endemicity of LF in the district. The per sample cost of purposive sampling for Mf was the lowest INR 41, followed by adult Mf sampling INR 93. Mini-TAS and MX were expensive with INR 659 and 812 respectively. The study demonstrates that though all the sampling methods could detect filarial infection above the threshold in high-risk areas, Mini-TAS could only detect infection in low-risk areas. Therefore, in the national programme Mini-TAS can be used as a decision-making tool to determine whether to exclude/ include a district having uncertain endemicity for MDA.